2012
DOI: 10.1002/jat.1789
|View full text |Cite
|
Sign up to set email alerts
|

Lead inhibits paraoxonase 2 but not paraoxonase 1 activity in human hepatoma HepG2 cells

Abstract: Lead is an environmental toxicant of great concern for humans and animals. Lead-induced liver damage and malfunction are partly due to a disturbance of the cellular antioxidant balance. Paraoxonase 1 (PON1) and PON2 are highly expressed in the liver and have been proposed as antioxidative enzymes. In this study, the effects of lead on PON1 and PON2 activities were investigated in human hepatoma HepG2 cells by exposing the cells to various concentrations of lead acetate for 24, 48, or 72 h. The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, another design was also done to evaluate the extract's protective impact on lead acetate-induced cell death. In review, the cells were pretreated at concentrations of 0–80 μ g/ml for 24 hours and then subjected to 100 μ g/ml of lead acetate [ 44 ] for a further 24 hours of coincubation. Afterward, 10 μ l of MTT reagent (5 mg/ml) was added to each well incubated for the next 3 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, another design was also done to evaluate the extract's protective impact on lead acetate-induced cell death. In review, the cells were pretreated at concentrations of 0–80 μ g/ml for 24 hours and then subjected to 100 μ g/ml of lead acetate [ 44 ] for a further 24 hours of coincubation. Afterward, 10 μ l of MTT reagent (5 mg/ml) was added to each well incubated for the next 3 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the established and dominant role of paraoxonases in cardiovascular diseases and relevant parameters, more recent studies revealed antioxidant and antiapoptotic activities of PON2 in cancers. 18 , 35 Several studies have indicated that PON2 is commonly upregulated in several tumor types, including pancreatic cancer, 20 , 36 hepatocellular carcinoma (HCC), 37 skin neoplasm, 21 , 38 prostate cancer, 39 and acute lymphoblastic leukemia. 40 , 41 A study reported that PON2 promotes cancer growth and metastasis in pancreatic cells by increasing cellular glucose uptake by modulating the GLUT1-mediated transport.…”
Section: Discussionmentioning
confidence: 99%
“…Centrifugation of the homogenate at 10 000 rpm for 15 min gave a clear supernatant which was collected into a new tube. 100 μg protein of the supernatant was incubated with 10 μM of each inhibitor (donepezil hydrochloride monohydrate for the AChE inhibitor, 45 ethopropazine hydrochloride for the BChE inhibitor, 46 naringenin for the PON1 inhibitor, 47 lead acetate for the PON2 inhibitor, 48 and bis(4-nitrophenyl) phosphate (BNPP) for the CE inhibitor). 37 The relative fluorescence intensity of 3 μM SE1 with each inhibitor was acquired after 15 min incubation.…”
Section: Methodsmentioning
confidence: 99%